Diazepam binding inhibitor governs neurogenesis of excitatory and inhibitory neurons during embryonic development via GABA signaling - Everlien, Isabelle; Yen, Ting-Yun; Liu, Yu-Chao; Di Marco, Barbara; Vázquez-Marín, Javier; Centanin, Lázaro; Alfonso, Julieta; Monyer, Hannah (Neuron, 2022)
Of the neurotransmitters that influence neurogenesis, gamma-aminobutyric acid (GABA) plays an outstanding role, and GABA receptors support non-synaptic signaling in progenitors and migrating neurons. Here, we report that expression levels of diazepam binding inhibitor (DBI), an endozepine that modulates GABA signaling, regulate embryonic neurogenesis, affecting the long-term outcome regarding the number of neurons in the postnatal mouse brain. We demonstrate that DBI is highly expressed in radial glia and intermediate progenitor cells in the germinal zones of the embryonic mouse brain that give rise to excitatory and inhibitory cells. The mechanism by which DBI controls neurogenesis involves its action as a negative allosteric modulator of GABA-induced currents on progenitor cells that express GABAA receptors containing γ2 subunits. DBI’s modulatory effect parallels that of GABAA-receptor-mediating signaling in these cells in the proliferative areas, reflecting the tight control that DBI exerts on embryonic neurogenesis.
Online verfügbar 22 August 2022, Artikelversion 5 Oktober 2022
Gesehen am 18.01.2023